Multi-field tuning of dielectric relaxation in epitaxial multiferroic hexaferrite thin film around room temperature: Property and mechanisms. Issue 20 (15th October 2022) - Liang, Guoqing; Xu, Sichen; Zhou, Hao; Su, Xiaodong; Zhao, Run; Yang, Hao; Tang, Rujun
Abstract: Understanding the dielectric relaxation properties of multiferroic hexaferrite thin films is crucial for device applications. This work investigates the dielectric relaxation characteristics (DRC) of multiferroic hexaferrite BaFe10.2 Sc1.8 O19 (BFSO) thin film under multi-fields. The alternative driving voltage and biasing voltage Vb were found to have significant effects on the DRC of BFSO/electrode interface dipoles, but negligible effects on the intrinsic dipoles in BFSO film. The DRC mechanism of a BFSO film capacitor under a magnetic field is opposite to that of Vb ; is dominated by intrinsic dipoles in BFSO, and is thermally activated. The temperature-dependent magnetodielectric spectra confirm that multiferroic dipoles in BFSO significantly impact the DRC of the capacitor, which is different from the DRC of nonmagnetic ceramic capacitors. The above findings can clarify the DRC mechanisms and integration of multiferroic hexaferrite thin films in magnetoelectric devices.